2020
DOI: 10.1051/0004-6361/202038456
|View full text |Cite
|
Sign up to set email alerts
|

A wide field-of-view low-resolution spectrometer at APEX: Instrument design and scientific forecast

Abstract: Context. Characterising the large-scale structure in the Universe from present times to the high redshift epoch of reionisation is essential to constraining the cosmology, the history of star formation, and reionisation, to measuring the gas content of the Universe, and to obtaining a better understanding of the physical processes that drive galaxy formation and evolution. Using the integrated emission from unresolved galaxies or gas clouds, line intensity mapping (LIM) provides a new observational window to m… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 57 publications
(19 citation statements)
references
References 46 publications
(45 reference statements)
0
19
0
Order By: Relevance
“…Overlaid are our predicted EoR-Spec sensitivities. Our proposed survey is as much as 10× more sensitive than other proposed surveys (TIME; Crites et al 2014;Sun et al 2021;CONCERTO;Concerto Collaboration et al 2020; raw sensitivities are shown for all experiments) leading to an expectation for detection of the intensity mapping signal at redshifts approaching 8 for most models. ALMA cannot make these measurements, since its field of view is smaller than a single pixel of EoR-Spec on FYST so that it requires enormous numbers of pointings to map the large spatial scales required for these measurements.…”
Section: Co Intensity Mapping From Present Day To the Peak Epoch Of S...mentioning
confidence: 68%
See 1 more Smart Citation
“…Overlaid are our predicted EoR-Spec sensitivities. Our proposed survey is as much as 10× more sensitive than other proposed surveys (TIME; Crites et al 2014;Sun et al 2021;CONCERTO;Concerto Collaboration et al 2020; raw sensitivities are shown for all experiments) leading to an expectation for detection of the intensity mapping signal at redshifts approaching 8 for most models. ALMA cannot make these measurements, since its field of view is smaller than a single pixel of EoR-Spec on FYST so that it requires enormous numbers of pointings to map the large spatial scales required for these measurements.…”
Section: Co Intensity Mapping From Present Day To the Peak Epoch Of S...mentioning
confidence: 68%
“…The resulting forecasts for the [C II] power spectrum span at least an order of magnitude, with the Serra et al (2016) forecasts on the more optimistic side, the Chung et al (2020) forecasts on the more conservative side, and the C. Karoumpis et al (2021, in preparation) forecasts spanning the range between them. However, even with these substantial uncertainties in the expected signal, we expect the fundamental sensitivity of the EoR-Spec survey (as shown in Figure 3; updated from Chung et al 2020 based on current estimates for FYST-DSS from Table 1, as well as more recent estimates for CONCERTO based on The CONCERTO collaboration et al 2020) to enable strong detections of [C II] emission anisotropies out to z ∼ 5. Nondetections at z  6 are possible outcomes, but would nonetheless be valuable in constraining a model space that is currently wide open.…”
Section: Methods To Derive Power Spectra and Cross Spectra From Raw Datamentioning
confidence: 98%
“…With between 50 and 500 individual MKIDs per pixel these arrays would have a very large detector count. A different approach to achieve at least medium energy resolution in this frequency range is to use a Martin-Puplett Interferometer (MPI) like the one suggested for the CONCERTO [53] instrument. CONCERTO, the CarbON CII line in post-rEionisation and ReionisaTiOn epoch instrument is a proposed MKID imaging spectrometer for the 12 m Apex telescope.…”
Section: Mkid Mid-ir To Microwave Imagersmentioning
confidence: 99%
“…A Martin-Puplett Interferometer (MPI) is a Fourier transform spectrometer which resembles a Michelson interferometer with an oscillating mirror at the end of one arm and can deliver a differential spectrum with respect to a given reference. With an oscillation frequency of 4 Hz, CONCERTO expects to achieve a resolution of 1 GHz across its 130-310 GHz (2.3-0.97 mm) band for a spectral resolving power R between 130 and 300 [53]. KISS (the KIDs Interferometer Spectrum Survey) [54,55] is a pathfinder instrument for CONCERTO and has recently been commissioned to the 2.25 m QUIJOTE telescope of Teide Observatory, Tenerife.…”
Section: Mkid Mid-ir To Microwave Imagersmentioning
confidence: 99%
“…In addition to 21cm line of hyperfine transition of neutral Hydrogen, LIM at mm/submm wavelengths, targeting spectral emission lines with rest-frame wavelengths in the far infrared (e.g., rotational lines of carbon monoxide CO(J→J-1) (Righi et al 2008;Lidz et al 2011;Breysse et al 2014;Mashian et al 2015;Li et al 2016;Padmanabhan 2018) and fine structure of ionized carbon [CII]) (Gong et al 2011a;Silva et al 2015;Pullen et al 2018;Padmanabhan 2019), has recently attracted a growing attention both in the context of galaxy/star formation (Gong et al 2011b;Kovetz et al 2020;Bernal & Kovetz 2022) and cosmology (Karkare & Schaan & White 2021a,b;Scott et al 2022). The wide array of pathfinder experiments such as CCAT-Prime (Chapman et al 2022), COMAP (Cleary et al 2021), CONCERTO (Ade et al 2020a), COPSS (Keating et al 2016), EX-CLAIM (Ade et al 2020b), mmIME (Keating et al 2020), SPT-SLIM (Karkare et al 2022b), TIME (Crites et al 2014a), are paving the way for future wide-field surveys capable of providing high-precision constraints on cosmology by providing robust detection of the line intensity power spectrum and constraining the astrophysical model dependencies of the signal. Establishing the science cases for future surveys and determining optimized survey strategies to achieve relevant theoretical thresholds is of uttermost importance.…”
Section: Introductionmentioning
confidence: 99%